Quelle maîtrise des compétences nécessaires à l’exercice de la fonction de maître de stage en Belgique francophone ? - Baco, Christophe; Derobertmasure, Antoine; Bocquillon, Marie; Demeuse, Marc (e-JIREF, 2021)
In French-speaking Belgium, the current reform of initial teacher training plans notably to improve the training of cooperating teachers, considering that they need specific training in the supervision of trainees to ensure their crucial role in the preparation of future teachers. In this context, a questionnaire was administered to 854 volunteer cooperating teachers. One of the purposes of this questionnaire was to allow them to self-assess their level of mastery of the tasks inherent to their function, which were included in a proposal of reference framework. This article analyzes the responses provided in order to test the structure of the six-competency reference framework proposed on the basis of a literature review. It also aims to compare the degree of mastery reported by different subgroups of respondents (e.g., cooperating teachers who have received training in supervising future teachers versus those who have not) to determine whether certain characteristics may be associated with a higher or lower degree of reported mastery. The results highlight four relevant dimensions of the role of cooperating teachers that have been documented in the scientific literature. They allow to formulate ways to improve the training of cooperating teachers.
Number: 1
Keywords: Formation initiale des enseignants; maîtres de stage; niveau de maîtrise déclaré; référentiel de compétences; stage